MANAJEMEN KEPALA SEKOLAH DALAM MENERAPKAN NILAI-NILAI ISLAM DI SD NEGERI 28 RAMBATAN - Suhaili. M (IAIN Batusangkar, 2016)
This qualitative study analyzed the management of principal on applying Islamic values in Primary School 28 Rambatan. The intruments in this study were interview, observation and documentation. The results showed that the management was done well. The programs applied in this primary school were speech, praying dhuha and praying dzuhur together, making wall magazine, scout, art contest, sport, social activity, and flag ceremony.Keywords: Management, Islamic Values, Primary School 28 Rambatan.